2020
DOI: 10.3390/ma13163629
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hot Workability of Nickel-Based Superalloy Using Activation Energy Map and Processing Maps

Abstract: The stress-strain curves for nickel-based superalloy were obtained from isothermal hot compression tests at a wide range of deformation temperatures and strain rates. The material constants and deformation activation energy of the investigated superalloy were calculated. The accuracy of the constitutive equation describing the hot deformation behavior of this material was confirmed by the correlation coefficient for the linear regression. The distribution of deformation activation energy Q as a function of str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The approaches based on DMM theory using criteria determining the material flow instability are an effective tool for describing the hot workability of the materials. The stability criterion developed by Prasad has shown its effectiveness in predicting the deformation behavior of many alloys [4,[39][40][41][42][43][44]. The distribution of power dissipation and flow instability parameters in the form of maps allows controlling changes in microstructure during the deformation of the investigated material.…”
Section: Processing Mapsmentioning
confidence: 99%
“…The approaches based on DMM theory using criteria determining the material flow instability are an effective tool for describing the hot workability of the materials. The stability criterion developed by Prasad has shown its effectiveness in predicting the deformation behavior of many alloys [4,[39][40][41][42][43][44]. The distribution of power dissipation and flow instability parameters in the form of maps allows controlling changes in microstructure during the deformation of the investigated material.…”
Section: Processing Mapsmentioning
confidence: 99%
“…As previously mentioned, according to the variation of -value, the deformation mechanisms corresponding to different processing parameter can be clarified. Generally, the -value corresponding to DRV mechanism is less than 0.25, the -value related to DRX mechanism is about 0.3–0.45, and, when -value exceeds 0.55, superplasticity may occur [ 4 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. However, the processing parameter domains with a higher -value are not always stable since an unstable deformation mechanism such as wedge cracking can also lead to higher -value.…”
Section: Clarification and Evaluation Of Deformation Mechanismsmentioning
confidence: 99%
“…Petr et al [ 8 ] investigated the correlation among flow stress, , and activation energy evolution of Cr-Mo low-alloyed steel, and they regarded the activation-energy processing maps as a tool for selection of processing parameters. Oleksandr et al [ 21 ] and Peng et al [ 22 ] respectively identified optimized hot processing parameters of nickel-based superalloy and homogenized Al-Zn-Mg-Cu alloy by a constructed conventional processing map and activation energy map of them under different true strains. Additionally, Quan et al [ 10 ] divided the processing parameter windows with DRX mechanism in an enhanced processing map, and clarified the desired processing parameter regions corresponding with DRX and lower activation energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Processing maps and dynamic material modeling [ 5 , 6 , 7 ] enable selecting appropriate parameters of thermomechanical processing of such steels and, as a result, obtaining good quality products having profitable mechanical properties and uniform microstructure. Much research in this area has been carried out in relation to aluminum alloys [ 8 , 9 ], titanium alloys [ 10 , 11 ], and nickel alloys [ 12 , 13 ]. In the design of structural parts widely used in the automotive and railroad industries, high-strength steels are becoming increasingly important [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%